Pain thresholds and intensities of CRPS type I and neuropathic pain in respect to sex - Meyer-Frießem, Christine; Attal, Nadine; Baron, Ralf; Bouhassira, Didier; Finnerup, Nanna B.; Freynhagen, Rainer; Gierthmuehlen, Janne; Haanpaa, Maija; Hansson, Per; Jensen, Troels S.; Kemp, Harriet; Kennedy, Donna; et al. (European journal of pain, 2020)
Background and Aims Healthy women have generally been found to have increased experimental pain perception and chronic pain has a higher prevalence in female as compared to male patients. However, no study has investigated whether pain intensity and pain perception thresholds are distinct or similar between sexes within various chronic pain entities. We investigated whether average pain intensities and pain thresholds assessed using quantitative sensory testing (QST) differed between women and men suffering from three distinct chronic pain conditions: Complex Regional Pain Syndrome (CRPS type I), peripheral nerve injury (PNI) or polyneuropathy (PNP), as compared to paired healthy volunteers. Methods QST data of 1,252 patients (669 female, 583 male) with PNI (n = 342), PNP (n = 571) or CRPS (n = 339), and average pain intensity reports from previously published studies were included. Absolute andz-values (adjusted for age and body region) of cold, heat, pressure (PPT) and pinprick pain thresholds were compared in generalized linear models with aetiology, duration of underlying pain disease and average pain intensity as fixed effects. Results Average pain intensity during the past four weeks did not differ between women and men, in both mean and range. In women absolute pain thresholds for cold, heat and pinprick were lower than in males across all diagnoses (p < .05). However, afterz-transformation these differences disappeared except for PPT in CRPS (p = .001). Discussion Pain thresholds in patients show only minor sex differences. However, these differences mimic those observed in healthy subjects and do not seem to be linked to specific pathophysiological processes. Significance Female healthy participants and female patients with neuropathic pain conditions or CRPS I report lower pain thresholds compared to males, but pain intensity is similar and there is no sex difference in the extent to which the thresholds are altered in neuropathic pain or CRPS. Thus, the sex differences observed in various chronic pain conditions mimic those obtained in healthy participants, indicating that these differences are not linked to specific pathophysiological processes and are of minor clinical relevance.
Gesehen am 23.04.2021